L'elevage en pays tropicaux - Dersch, D. (1986)
Reports findings of a survey on the role, ownership and composition of livestock in the Ethiopian highlands to determine the production capability and potential of indigenous zebu cow under traditional smallholder management. Discussions on dairy husbandry and management, dairy performance, animal health and constraints to agricultural development in these systems are included. Data on production performance indicate quantities of milk yield and composition, and utilisation in the Debre Berhan Area.